Analisis Varian Biaya Produksi sebagai Alat Pengendalian Manajemen pada UD Wijaya Pabrik Krecek Uyel - Viska Berliyanti; Sigit Puji Winarko; Andy Kurniawan (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze production cost variances, identify the factors causing production cost variances, and determine the role of production cost variance analysis as a management control tool at UD Wijaya Pabrik Krecek Uyel. This study employed a descriptive quantitative method with a descriptive quantitative approach. The data used consisted of 2024 production cost data, including direct material costs, direct labor costs, and manufacturing overhead costs. Data analysis was conducted using variance analysis by comparing standard costs with actual costs to identify cost deviations and evaluate the effectiveness of management control. The results indicate that during the period from January to December 2024, both favorable and unfavorable production cost variances occurred. However, overall, unfavorable variances were more dominant, indicating that actual production costs tended to exceed the standard costs established by the company. The largest variance occurred in December, amounting to IDR 6,600,000. The production cost variances were primarily caused by increases in raw material prices, higher direct labor costs, and rising manufacturing overhead costs as production activities increased. The findings also reveal that production cost control at UD Wijaya Pabrik Krecek Uyel has not yet been implemented optimally. Nevertheless, production cost variance analysis can serve as an effective management control tool because it provides information on cost deviations, assists in evaluating the efficiency of resource utilization, and serves as a basis for corrective actions to improve production cost efficiency in subsequent periods.